Mechanical complications and infection control comparison of custom-made and prefabricated articular hip spacers in the treatment of periprosthetic infection - Emmer, Jan; Tomáš, Tomáš; Apostolopoulos, Vasileios; Brančík, Pavel; Rapi, Jakub; Nachtnebl, Luboš (Joint diseases and related surgery, 2023)
OBJECTIVES: The purpose of our study was to compare the complication rate and the outcomes of custom-made spacers (C-spacers) and prefabricated articular spacers (P-spacers) in the treatment of periprosthetic infection. PATIENTS AND METHODS: In this retrospective study, 78 patients (44 females, 34 males; mean age: 68.5±9.48 years; range, 47 to 82 years) with articular spacers implanted in our institution were analyzed between January 2009 and December 2019. We recorded implant results as per mechanical complications, infection control, the interval from surgery to definitive hip replacement, and the rate of achieving recovery of joint function after stage two arthroplasty. RESULTS: There were 29 revised spacers; 18 of them were C-spacers and 11 were P-spacers (p=0.0383). A total of 16 dislocations were recorded, of which six were dislocations of C-spacers, and 10 were dislocations of P-spacers (p=0.0082). Additionally, we registered four spacer breakages, all of which occurred in C-spacers (p=0.295). C-spacers failed early, at an mean interval of 2.2 weeks after implantation, and P-spacers failed later, with an mean of 9.3 weeks after implantation (p=0.0187). A total of nine reinfection complications of spacers were registered; only one infection of P-spacers, and eight infections related to C-spacers (p=0.2583). Definitive revision total hip arthroplasty (rTHA) after spacer explantation and successful treatment of the infection occurred in 63 cases out of 78 patients. Definitive rTHA occurred after the use of C-spacers in 41 (78%) patients and after the use of C-spacers in 22 (84%) patients (p=0.7816). C-spacers had a mean interval from spacer implantation to definitive rTHA of 6.56±6.03 months, and P-spacers had a mean interval of 4±1.93 months (p=0.0164). CONCLUSION: Custom-made spacers were shown to have lower mechanical complication rates than prefabricated ones but more infection complications. Prefabricated spacers had more dislocations and fewer breakages. Custom-made spacer mechanical failures occurred earlier compared to prefabricated ones.
Keywords: Male; retrospektivní studie; dislokace kloubu; náhrada kyčelního kloubu; Infection Control; Aged; mužské pohlaví; senioři; odstranění implantátu; Device Removal; kontrola infekce; lidé; Arthroplasty, Replacement, Hip; ženské pohlaví; Humans; Retrospective Studies; Female; lidé středního věku; Joint Dislocations; Middle Aged